Biological Impact of the TSHβ Splice Variant in Health and Disease - Klein, John R. (Frontiers in Immunology, 2014)
Thyroid stimulating hormone (TSH), a glycoprotein hormone composed of alpha and beta chains, is produced by thryrotrope cells of the anterior pituitary. Within the conventional endocrine loop, pituitary-derived TSH binds to receptors in the thyroid, resulting in the release of the thyroid hormones thyroxine (T4) and triiodothyronine (T3). T4 and T3 in turn regulate nearly every aspect of mammalian physiology, including basal metabolism, growth and development, and mood and cognition. Although TSH-beta has been known for years to be produced by cells of the immune system, the significance of that has remained largely unclear. Recently, a splice variant of TSH-beta (TSH-beta-v), which consists of a truncated but biologically functional portion of the native form of TSH-beta, was shown to be produced by bone marrow cells and peripheral blood leukocytes, particularly cells of the myeloid/monocyte lineage. In contrast, full-length native TSH-beta is minimally produced by cells of the immune system. The present article will describe the discovery of the TSH-beta-v and will discuss its potential role in immunity and autoimmunity, inflammation, and bone remodeling.